Peptidomic Analysis of Neonate Umbilical Cord Blood for the Identification of Endogenous Peptides Involved in Hypoxic–Ischemic Encephalopathy - Dong, Xiaohua; Zhao, Jing; Shen, Yinyin; Sun, Qing; Wu, Xiaohui; Zhu, Yanqing; Yu, Lingling; Zhao, Yingmin (Frontiers in Pediatrics, 2021)
Neonatal hypoxic-ischemic encephalopathy (HIE) is a common neurological disorder triggered by perinatal cerebral ischemia and hypoxia. Accumulating evidence has shown that peptides have neuroprotective effects in nerve injury. However, the function of endogenous peptides in the pathogenesis of HIE has not been studied. In the present study, a comparative peptidomic profile was performed in the serum of human umbilical cord blood with HIE (3 patients) and the control group (3 healthy controls) by liquid chromatography-mass spectrometry (LC-MS). Our study demonstrated that a total of 49 peptides derived from 25 precursor proteins were differentially expressed in the serum of HIE compared with normal controls, including 33 upregulated peptides and 16 downregulated peptides. Each of the differentially expressed peptides has specific characteristics, including pI, Mw and cleavage pattern. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that the precursor proteins of differentially expressed peptides participate in different biological processes. Moreover, among the 49 differentially expressed peptides, 21 peptides were identified from the fibrinogen chain family, which plays a role in neurological diseases, suggesting that these peptides may play an important role in maintaining brain health. In conclusion, our results showed a comparative peptidomic profile from human umbilical cord blood of HIE patients and normal controls. These dysregulated peptides have potentially important functions in umbilical cord blood with HIE and may be involved in the pathogenesis of HIE.